Workplace Stressors and Coping Strategies Among Public Hospital Nurses in Medan, Indonesia - Fathi, Achmad; Nasae, Tasanee; Thiangchanya, Pratyanan (Nurse Media Journal of Nursing, 2012)
Background: Nursing is considered as a stressful job when compared with other jobs. Prolonged stress without effective coping strategies affects not only nurses’ occupational life but also their nursing competencies. Medan is the biggest city in Sumatera Island of Indonesia. Two tertiary public hospital nurses in this city hold the responsibility in providing excellent care to their patients. Objective: To investigate the relationships between the nurse’s workplace stressors and the coping strategies used. Method: The descriptive correlational study was conducted to examine the relationships between workplace stressors and the coping strategies used in nurses of two public hospitals in Medan. The sample size of 126 nurses was drawn from selected in-patient units. Data were collected by using self-report questionnaires and focus group interview. The majority of subjects experienced low workplace stressors, where death/dying was the most commonly reported workplace stressor followed by workload. Religion was the most commonly used coping strategy. Result: Significant correlations were found between subscales of workplace stressors and coping strategies. Most of subjects used emotion-focused and dysfunctional coping strategies rather than problem-focused coping strategies. Conclusion: The nurse administrators in the hospitals need to advocate their in order to use problem-focused coping strategies more frequent than emotion-focused and dysfunctional coping strategies when dealing with workplace stressors. Keywords: workplace stressor, coping strategy, public hospital nurses